Drug‐induced photosensitivity: new insights into pathomechanisms and clinical variation through basic and applied science. (28th February 2017) - Khandpur, S.; Porter, R.M.; Boulton, S.J.; Anstey, A.
Abstract : What's already known about this topic? Drugs that can absorb light (mostly ultraviolet A) can lead to photosensitivity in some patients. A potential mechanism for phototoxicity is via the generation of higher levels of reactive oxygen species (ROS). What does this study add? Despite measures to test drugs for potential photoreactivity, new drugs are still emerging that can cause photosensitivity. There are a number of reasons why some patients may not cope with the increased ROS levels that could explain their susceptibility to drug‐induced photosensitivity. Linked Comment:Ibbotson. Br J Dermatol 2017;176 :850–851 Summary: Drug‐induced photosensitivity occurs when a drug is capable of absorbing radiation from the sun (usually ultraviolet A) leading to chemical reactions that cause cellular damage (phototoxicity) or, more rarely, form photoallergens (photoallergy). The manifestation varies considerably in presentation and severity from mild pain to severe blistering. Despite screening strategies and guidelines in place to predict photoreactive drugs during development there are still new drugs coming onto the market that cause photosensitivity. Thus, there is a continuing need for dermatologists to be aware of the different forms of presentation and the culprit drugs. Management usually involves photoprotection and cessation of drug treatment. However, there are always cases where the culprit drug is indispensable. The reason why some patients are susceptible while others remain asymptomatic is not known. A potential mechanism for the phototoxic reactions is the generation of reactive oxygen species (ROS), and there are a number of reasons why some patients might be less able to cope with enhanced levels of ROS.